Proces zmian systemowych w podmiotach opieki zdrowotnej na przykładzie regionu południowo-zachodniej Polski - Januszewska, Małgorzata; Nawrocka, Elżbieta (The Process of System Changes in Health Care Institutions - the Region of South-Western Poland as an Example, 2005)
The article deals with problems of restructuring health care institutions in Lower Silesia region. It describes theoretical assumptions of system changes and the subjective structure transformations of health care institutions in the studied province. In order to make the analysis more detailed a survey was conducted, which covered the total, general population of independent, public, health care institutions located in south-western part of the discussed region, which provide, among others, hospitalization services. Conclusions are included at the end of the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 236-250